Perancangan Sistem Otomatis Pemberi Pakan Ikan Berdasarkan Usia Berbasis IoT - Ios Jakub Sitompul; Habib Satria; Moranain Mungkin (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2023)
Cultivating catfish uses an artificial pond which is in great demand among the community. Most of the people who have jobs other than breeders choose this job to increase their income. Today's technological developments and advancements have a significant impact on how human society conducts every action. The authors created a program and were interested in using the term "Design of Automatic Catfish Feeders Based on IoT-Based Age" based on the background described above. This tool system makes use of the NodeMCU ESP8266 microcontroller, which performs dual roles as a WI-FI network receiver and a data processor for a WI-FI network system. This tool system uses the RTC module as a time reader to provide fish feed automatically in the morning and evening and this tool system can then be controlled using a smartphone and the NodeMCU application to provide feed using the IOT system.